Missense Mutations in FDNC5 Associated with Morphometric Traits and Meat Quality in Hainan Black Goats - Jing Huang; Mengning Xu; Yuelang Zhang; Jiancheng Han; Hanlin Zhou; Ke Wang (Animals)
Goats are widely recognized for their adaptability and resource efficiency, making them an excellent choice for sustainable farming. However, the Hainan Black goat (HNBG), a vital breed in southern China’s tropical regions, faces significant challenges that threaten its productivity and economic viability. Specifically, young HNBGs exhibit stunted growth and poor muscle development, indicating the breed may have more genetic defects that cause the poor phenotypes. The FNDC5 gene, which encodes the protein irisin, plays a key role in promoting mitochondrial biogenesis and oxidative metabolism by activating critical signaling molecules such as PGC-1α, thereby enhancing muscle endurance and metabolic efficiency. This study aimed to investigate the impact of missense mutations in the FNDC5 gene on growth and meat quality traits in HNBGs. We sequenced a population of HNBGs and identified three SNPs that could lead to amino acid substitutions. Notably, SNP1 (p.119A/V) and SNP2 (p.135R/H) showed strong linkage. Predictions on the structural effects of these mutations indicated that SNP1 (p.119A/V) and SNP3 (p.170W/G) could alter the secondary structure of the FNDC5 protein. Association analyses revealed that SNP1 (p.119A/V) and SNP2 (p.135R/H) were significantly associated with morphometric traits and meat quality. The phenotypic values of SNP1 and SNP2 co-mutants were significantly lower than those of other combined genotypes. Furthermore, gene expression levels of FNDC5 varied notably across individuals with different SNP1 genotypes. These findings suggest that FNDC5-SNP1 (p.119A/V) could serve as a promising genetic marker for selecting HNBGs with improved growth and muscle development, offering a potential pathway for enhancing key economic traits in this breed.